Heat transfer performance evaluation in circular tubes via internal repeated ribs with entropy and exergy analysis. (5th November 2018) - Sayed Ahmed, Sayed Ahmed E.; Ibrahim, Emad Z.; Ibrahim, Mostafa M.; Essa, Mohamed A.; Abdelatief, Mohamed A.; El-Sayed, Mohamed N.
Highlights: Performance evaluation of various internal repeated ribs was examined. The effect of changing ribs shape, depth and pitch were considered. A new correlation for performance criteria with variable parameters was developed. Prominent comprehensive evaluations of entropy and exergy analysis were performed. The dominance of generated vortices and flow phenomena was analyzed. Abstract: In the present study, heat transfer enhancement in circular tubes via internal repeated ring-type ribs is, numerically, investigated and validated with experimental data obtained by Huang et al. (2015). Thermal evaluation is also done for tubes with rectangular, trapezoidal and triangular ribs. Furthermore, entropy and exergy analysis are performed on all the tested tubes. Air is used as the working fluid at (3.6 × 10 3  ≤ Re ≤ 1.65 × 10 4 ). The rib-depth to tube-inner diameter ratio (e/d) and the rib-pitch to tube-inner diameter ratio (p/d) in the tubes ribs configurations are considered. The performance evaluation criterion (PEC) is employed to estimate the optimum case that gives high thermal hydraulic efficiency (THE). It is found that the best (THE) accompanying with lower entropy and higher exergy are achieved for the tube with ring-type ribs compared to other shapes. The flow phenomena, temperature and pressure contours are illustrated with a consistent evaluation.